KEADILAN PEMILU DAN PERGESERAN DEMOKRASI, SEBUAH ANALISA ATAS PELAKSANAN PEMILU 2019 DAN MASA DEPAN PEMILU - Kaka Suminta (Jurnal Bawaslu Provinsi Kepulauan Riau, 2019)
Democracy only survive if they provide effective government, that require three connected condition, First there be a relativemajority agreement on main direction of policy toward security, growth and walfare. Second, is constitutional and limit the power of majority. And Third, the whole p[olitical process must be underpinned by the wide spread loyalty to democratic values and the continukity the democratic process itself.